2004
DOI: 10.1577/t03-091.1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Fingerprints for Lake Superior Coastal Wetlands Derived from Elemental Analysis of Yellow Perch Otoliths

Abstract: Assessing the ecological importance of coastal habitats to Great Lakes ecosystems requires an understanding of the ecological linkages between coastal and offshore waters. Elemental analysis of fish otoliths has emerged as a powerful technique that can provide a natural tag for determining nursery area affiliation, population structure, and movement of individual fish. Since the elemental composition of fish otoliths reflects some of the environmental conditions under which a fish was reared, otolith chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 32 publications
7
66
1
4
Order By: Relevance
“…Our findings corroborate those of a few other recent studies that demonstrated that otolith microchemistry and isotopic analysis represent powerful techniques for retrospectively describing the environmental history of fishes that reside solely in freshwaters, including lakes (Joukhadar et al 2002;Brazner et al 2004;Munro et al 2005;Ludsin et al 2006), streams (Wells et al 2003), and small rivers (Bickford and Hannigan 2005). The results of this study demonstrate that otolith elemental and isotopic assays can also be applied to gain valuable insight into fish movement between large rivers and associated lentic floodplain habitats that would be difficult to obtain by other means.…”
Section: Relation Between Fish Age and Source Habitat And Implicationsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings corroborate those of a few other recent studies that demonstrated that otolith microchemistry and isotopic analysis represent powerful techniques for retrospectively describing the environmental history of fishes that reside solely in freshwaters, including lakes (Joukhadar et al 2002;Brazner et al 2004;Munro et al 2005;Ludsin et al 2006), streams (Wells et al 2003), and small rivers (Bickford and Hannigan 2005). The results of this study demonstrate that otolith elemental and isotopic assays can also be applied to gain valuable insight into fish movement between large rivers and associated lentic floodplain habitats that would be difficult to obtain by other means.…”
Section: Relation Between Fish Age and Source Habitat And Implicationsupporting
confidence: 90%
“…However, otolith microchemistry and isotopic analysis have also recently proven useful in studies of fish origins and environmental history within freshwater systems (e.g., Kennedy et al 1997;Wells et al 2003;Brazner et al 2004). In this paper, we describe how we used a natural marker (otolith Sr:Ca ratio) that has previously been applied to detect residence in environments that differ greatly in salinity (e.g., Kalish 1990;Limburg 2001) in conjunction with the first application of stable hydrogen isotope analysis of otoliths (Whitledge et al 2006) to determine sources (floodplain pond versus riverine habitats) of nonnative centrarchid fishes, namely, largemouth bass Micropterus salmoides, green sunfish Lepomis cyanellus, bluegill L. macrochirus, and black crappie Pomoxis nigromaculatus, in the upper Colorado River.…”
mentioning
confidence: 99%
“…Ca concentrations and otolith weights (OWs) are highly correlated above a certain threshold (Brazner et al 2004). Below this threshold, there is seemingly no relationship between OW and Ca concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Certaines ont tenté plus particulièrement de mettre en relation la composition élémentaire des otolithes avec celle de l'eau (Bath et al, 2000;Elsdon et Gillanders, 2003;Milton et Chenery, 2001 (Brazner et al, 2004b). Jusqu'à présent, l'empreinte élémentaire a surtout été utilisée en milieux marins (Brown, 2006;Campana et al, 2007;Clarke et al, 2009;Cook, 2011;Edmonds et al, 1991;Fodrie et Herzka, 2008;Gillanders et Kingsford, 1996;Humphreys Jr et al, 2005;Lawton et al, 2010;Rooker et al, 2002;Thorrold et al, 2007), dans certains estuaires (Bradbury et al, 2011;Brown, 2006;Gillanders et Kingsford, 1996;Hobbs et al, 2007;Swearer et al, 2003) et seulement quelques recherches comparables ont été menées en eaux douces avec succès (Brazner et al, 2004a;Brazner et al, 2004b;Fisher et al, 1999;Whitledge, 2009;Zeigler et Whitledge, 2010;Zeigler et Whitledge, 2011;Zitek et al, 2010). heures pour un séchage complet, puis rangées dans une boîte en vue de procéder aux analyses à l'aide d'un spectromètre de masse couplé à un plasma inductif (Tableau 2).…”
Section: Remerciementsunclassified